Proyeksi Peningkatan Penjualan Motor Merk Honda Dengan Metode Least Square - Noorlaily Maulida; Periyadi Periyadi; Dewi Ariefahnoor (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
In determining sales targets, each Dealer determines sales targets only based on previous sales, without any fixed calculation method. The aim of this research is to find a calculation method that is considered closest, so that it can be used to determine sales targets for the next period. The sample studied was sales of automatic motorbikes in October, November and December for the 2022 period, using actual company sales data as a reference as a comparison. The research results show that the Least Square Method can be implemented as a fixed calculation to determine sales targets for Honda brand motorbikes, with an average MAPE value of 5.3% or an accuracy value of 94.7%.